Validated High Performance Liquid Chromatography Method for Simultaneous Estimation of Paracetamol and Aceclofenac in Tablet Dosage Forms - HARIKRISHNAN*, N.; GUNASEKARAN, V.; SATHISHBABU, A.; SRINIVASARAO, G.; ROOSEWELT, C. (Asian Journal of Chemistry, 2010)
A simple, specific, precise and rapid HPLC method has been developed for estimation of paracetamol and aceclofenac simultaneously in tablet dosage form. In this method standard solution and sample solution of paracetamol and aceclofenac were applied on C18 reversed phase column with a mobile phase consisting of methanol, buffer, water and acetonitrile (85:15:25:5 v/v/v/v) at a flow rate of 1 mL/min and spectrophotometric detection was carried out at 274 nm. This HPLC system was quantitatively evaluated in terms of linearity, accuracy, precision, repeatability and specificity proving the utility in estimation of drug content in tablet dosage forms.